2019
DOI: 10.3390/rs11232873
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Within-Field Variability of Corn Yield using Sentinel-2 and Machine Learning Techniques

Abstract: Monitoring and prediction of within-field crop variability can support farmers to make the right decisions in different situations. The current advances in remote sensing and the availability of high resolution, high frequency, and free Sentinel-2 images improve the implementation of Precision Agriculture (PA) for a wider range of farmers. This study investigated the possibility of using vegetation indices (VIs) derived from Sentinel-2 images and machine learning techniques to assess corn (Zea mays) grain yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(105 citation statements)
references
References 59 publications
16
70
0
Order By: Relevance
“…Considering the test dataset, the RF regression had RMSE values ranging from 4.63 to 5.47 Mg ha −1 , which was lower than the MLR model (RMSE closer to 6.0 Mg ha −1 ). Other studies reported RF prediction as more accurate than MLR [2,53].…”
Section: Selection Of Predictor Variablesmentioning
confidence: 98%
See 1 more Smart Citation
“…Considering the test dataset, the RF regression had RMSE values ranging from 4.63 to 5.47 Mg ha −1 , which was lower than the MLR model (RMSE closer to 6.0 Mg ha −1 ). Other studies reported RF prediction as more accurate than MLR [2,53].…”
Section: Selection Of Predictor Variablesmentioning
confidence: 98%
“…Orbital images are commonly used in agriculture to identify spectral variations resulting from soil and crop characteristics at a large-scale, supporting diagnostics for agronomical crop parameters and helping farmers to make better management decisions. For example, over the years, orbital images were used to delimit management zones for annual crops [1], monitor within-field yield variability for many crops such as corn [2] and cotton [3], map vineyard variability [4], plan the wheat harvest [5], develop crop growth model [6], and map grasslands biomass [7,8], among others. Some of the main limitations related to orbital images are the lack of ground truth data (calibration) and the measurement accuracy of the agronomical variables [9].…”
Section: Introductionmentioning
confidence: 99%
“…The simple linear model was used as a benchmark to measure the relative performance of the models implemented. The other models (xgbTree, nnet, rf) evaluated in this work were selected based on the robustness they displayed in previous studies [4,5,59,60].…”
Section: Plos Onementioning
confidence: 99%
“…The modelling process implemented herein-machine learning techniques-were used to predict yields like in similar approaches currently used to develop agricultural models based on remote sensing imagery [70][71][72]. According to [60], machine learning techniques provide a higher accuracy and a more robust performance compared to conventional correlations as they learn to model complexity through training. In addition, remote sensing models to forecast crop yields can perform comparably or better than complex crop simulation models [4].…”
Section: Plos Onementioning
confidence: 99%
“…Several studies on spectral data applications in field crops are available from remote and ground sensors using data-mining techniques for nitrogen status and grain yield [20,21]. Most of these studies were based on measurements acquired by one sensor and there is a lack of available information on how different combinations of sensors are informative.…”
Section: Winter Wheatmentioning
confidence: 99%